Workplace health and safety issues among community nurses: a study regarding the impact on providing care to rural consumers. Issue 8 (12th August 2015) - Terry, Daniel; Lê, Quynh; Nguyen, Uyen; Hoang, Ha
Abstract : Objectives: The objective of the study was to investigate the types of workplace health and safety issues rural community nurses encounter and the impact these issues have on providing care to rural consumers. Methods: The study undertook a narrative inquiry underpinned by a phenomenological approach. Community nursing staff who worked exclusively in rural areas and employed in a permanent capacity were contacted among 13 of the 16 consenting healthcare services. All community nurses who expressed a desire to participate were interviewed. Data were collected using semistructured interviews with 15 community nurses in rural and remote communities. Thematic analysis was used to analyse interview data. Results: The role, function and structures of community nursing services varied greatly from site to site and were developed and centred on meeting the needs of individual communities. In addition, a number of workplace health and safety challenges were identified and were centred on the geographical, physical and organisational environment that community nurses work across. The workplace health and safety challenges within these environments included driving large distances between client's homes and their office which lead to working in isolation for long periods and without adequate communication. In addition, other issues included encountering, managing and developing strategies to deal with poor client and carer behaviour; working within and negotiating working environments such as the poor condition of patient homes and clients smoking; navigating animals in the workplace; vertical and horizontal violence; and issues around workload, burnout and work-related stress. Conclusions: Many nurses achieved good outcomes to meet the needs of rural community health consumers. Managers were vital to ensure that service objectives were met. Despite the positive outcomes, many processes were considered unsafe by community nurses. It was identified that greater training and capacity building are required to meet the needs among all staff.